2021
DOI: 10.1039/d0sm01570a
|View full text |Cite
|
Sign up to set email alerts
|

How ambient conditions affect the Leidenfrost temperature

Abstract: By sufficiently heating a solid, a sessile drop can be prevented from contacting the surface by floating on its own vapour. While certain aspects of the dynamics of this so-called...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 44 publications
(77 reference statements)
0
6
0
Order By: Relevance
“…1(a)]. Further experiments [17][18][19][20] confirmed the metastability of the levitated state and showed that the lower threshold of the Leidenfrost temperature T − L is controlled by hydrodynamic instabilities of the gas layer, or by surface contamination and/or roughness. On the contrary, measuring T þ L is still challenging because of the hysteresis introduced by the hydrodynamic stability of the vapor layer and only recently attempts have been made to derive T þ L from a stability analysis at the nanoscale [21].…”
mentioning
confidence: 83%
“…1(a)]. Further experiments [17][18][19][20] confirmed the metastability of the levitated state and showed that the lower threshold of the Leidenfrost temperature T − L is controlled by hydrodynamic instabilities of the gas layer, or by surface contamination and/or roughness. On the contrary, measuring T þ L is still challenging because of the hysteresis introduced by the hydrodynamic stability of the vapor layer and only recently attempts have been made to derive T þ L from a stability analysis at the nanoscale [21].…”
mentioning
confidence: 83%
“…Pressure dependence. Interestingly, the Leidenfrost temperature depends on p 0 for the quasi-static case, but this can be attributed to the thermodynamics (van Limbeek et al 2021). The dynamic Leidenfrost temperature also depends on ambient pressure (van Limbeek et al 2018), and the picture there is less clear and deserves further attention, with lower pressures leading to an unexplained increased dependence of T L on impact speed.…”
Section: Phenomenology Of the Film And Modes Of Touchdownmentioning
confidence: 97%
“…The condition ṽg i = Ti corresponds to the fact that k changes its sign. The value of T w associated with bifurcation (26) is our definition of the Leidenfrost temperature which will be denoted by T L . From the Table III For the second linear approximation (37) the corresponding Table IV is formed.…”
Section: B Values Of Latent Heat Of Vaporization For Watermentioning
confidence: 99%
“…These events have given rise to a large number of studies [1][2][3][4][5][6][19][20][21][22][23][24]. In particular, the Leidenfrost temperature depends on physico-chemical and mechanical properties of the heated surface, the liquid type and the ambient conditions [25,26]. However, it cannot be said that a theory for a satisfactory prediction of the Leidenfrost temperature has been given.…”
Section: Introductionmentioning
confidence: 99%